If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(2p + -5) = 13 + -4p Reorder the terms: -1(-5 + 2p) = 13 + -4p (-5 * -1 + 2p * -1) = 13 + -4p (5 + -2p) = 13 + -4p Solving 5 + -2p = 13 + -4p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '4p' to each side of the equation. 5 + -2p + 4p = 13 + -4p + 4p Combine like terms: -2p + 4p = 2p 5 + 2p = 13 + -4p + 4p Combine like terms: -4p + 4p = 0 5 + 2p = 13 + 0 5 + 2p = 13 Add '-5' to each side of the equation. 5 + -5 + 2p = 13 + -5 Combine like terms: 5 + -5 = 0 0 + 2p = 13 + -5 2p = 13 + -5 Combine like terms: 13 + -5 = 8 2p = 8 Divide each side by '2'. p = 4 Simplifying p = 4
| x-4(2x+1)=2x-6 | | [m+5]+9=-16 | | 100*k=0.15 | | -3x+4=-6x+16 | | 60=a/1-.4 | | (5x-5)+(8x-48)=180 | | V=1/3*3.14*rx^2*h | | 2x+3y=4fory | | -5x^2+7x-10=0 | | [m+5]+9=16 | | X=4y-25 | | =4*3*3 | | 3/9=4/r-s | | 0.6v+2.1=17 | | X^3+px^2+px+1=0 | | (Y)(Y)=0 | | 6/9=n/3 | | 2x-6=9x+9 | | 2X-5y-3xy=0 | | 16x^2+70x-9=(Ax+B)(Cx-D) | | |4x-1/3|=1 | | 2x^2-16=20 | | 2X-0.5y-0.001xy=0 | | 502.4=3.14*4x^2*h | | 49w^2-25f^2= | | 2x+6=4x+20 | | .06x=1 | | (-1)-3-(-11)+(-9)= | | 5x-3(x-6)=3+3x | | -2xt^2-11=5 | | X^2+2x+2.5=0 | | 3+2x+11=6x+33 |